In Vitro Activity of the New Triazole BMS-207147 against Aspergillus Species in Comparison with Itraconazole and Amphotericin B - Moore, Caroline B. (American Society for Microbiology, 2000)
The in vitro activity of BMS-207147 against 80 clinical isolates of Aspergillus was compared with that of itraconazole and amphotericin B, using a validated microtiter method. Geometric mean MICs (in μg/ml) were as follows: 1.71 for BMS-207147, 0.67 for itraconazole, and 0.63 for amphotericin B. The range of concentrations of each drug was 0.125 to >16 μg/ml. Aspergillus fumigatus was significantly more susceptible to BMS-207147 (P < 0.05) than A. terreus and A. flavus. No BMS-207147-resistant A. fumigatus isolates were identified, though eight itraconazole-resistant (MIC, >8 μg/ml) isolates were. BMS-207147 is active against Aspergillus spp. at slightly high concentrations compared with itraconazole and amphotericin B.